Hydrolysis With Two Enzymes in Edible Fern (Diplazium esculentum) as a Source of Flavours - Kartikasari, Subekah Nawa; Witono, Yuli; Handoyo, Tri; Santoso, Umar (Indonesian Food Science and Technology Journal, 2024)
Ferns (Diplazium esculentum) had high content of proteins, fats, flavonoids, and polyphenols, especially in young fern leaves. Its potential to developed as a source vegetable flavour. Currently, understanding about fern flavor processing technologies and the potential of ferns for health is still relatively limited, especially on local Indonesian fern. This research aims to know about morphological characteristics of Indonesian local fern vegetables (Mloko Jember, Air Jember, and Ayam Banyuwangi), and determined the effect of processing to its chemical characteristics and volatile compound, then hydrolyzed enzymes to produce non-volatile flavours. Ferns are processed by steaming, drying, and control methods and are hydrolyzed by combining two enzymes - bromelain and protease, with a pH of 7 and temperature of 55 0C for 1 hour. The result showed that the morphology of the three fern are different in the shape of shoot and plant based on their location. The researchers discovered that enzymatically hydrolyzing the proteins in local fern vegetables  using two enzymes (bromelain and protease) produced amino acid components such as aspartic acid and glutamic acid. These have MSG-like flavour.